WORKSHOP FOR DRAFTING AND DELIVERY OF ECONOMIC SCIENTIFIC ARTICLES FOR IMPROVEMENT AND DEVELOPMENT OF SOCIAL STATISTIC INDICATORS - Nila Kesumawati; Depi Pramika (Universitas Muhammadiyah Mataram, 2021)
Abstrak: Tujuan dari kegiatan pengabdian ini untuk melaksanakan tri darma perguruan tinggi serta penyususnan dan pengiriman artikel ilmiah ekonomi bagi peserta untuk penyempurnaan dan pengembangan indikator statistik sosial BPS Provinsi Sumatera Selatan. Metode pelaksanaan kegiatan Pengabdian kepada Masyarakt (PkM) ini dilaksanakan dengan menggunakan metode ceramah, tanya jawab dan workshop atau praktek penyusunan dan pengiriman artikel ilmiah ekonomi. Pelaksanaan kegiatan dilakukan selama satu hari. Hasil kegiatan menunjukkan selama kegiatan berlangsung terjadi iteraksi timbal balik yang baik antara pemateri dan peserta, dimana peserta sangat aktif dan antusias dalam menyimak dan bertanya mengenai materi yang dipaparkan dan perperan aktif dalam menyusun artikel dan langsung praktek dalam pengiriman artikel ilmiah ekonomi yang diinginkan. Selain itu juga dengan adanya kegiatan ini peserta sudah dapat mengetahui bagaimana menyusun dan mengirim artikel ilmiah ekonomi serta mengetahui jurnal-jurnal yang akan menjadi rujukan dalam mempublikasikan artikel ilmiah yang sudah disusun.Abstract: The aim of this service activity is to carry out the tri darma of higher education as well as the compilation and delivery of economic scientific journals for participants to improve and develop social statistical indicators of BPS South Sumatra Province. The method of implementing Community Service activities (PkM) is carried out using the method of lectures, questions and answers and workshops or the practice of compiling and sending economic scientific journals. The activities are carried out for one day. The results of the activity showed that during the activity there was a good reciprocal reaction between the presenters and the participants, where participants were very active and enthusiastic in listening and asking questions about the material presented and playing an active role in compiling journals and direct practice in sending the desired economic scientific journals. In addition, with this activity, participants can already know how to compile and send economic science journals as well as find out which journals will be a reference in publishing scientific articles that have been compiled.